Living Hadis di Kampung Madinah, Temboro, Magetan - Muhammad Rasyied Awabien (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Temboro Village is located in Magetan, East Java, has a unique Islamic life. In this village, almost the entire community tried to imitate the life and Islamic life of the people of Madinah. This is evidenced from how to dress and the habit of hastening prayer in the mosque and closing the shop when prayer time arrives. Although the style of dress wearing a niqab for women and wearing special trousers for men, Islam in the village of Temboro is considered not radical. Based on interviews and observations, it was found that the Islamic style in Temboro Village was oriented towards the Jama'ah Tabligh and had a large positive impact. The living quran approach used is able to reveal that religious life in Temboro Village has experienced a significant shift. In addition, the economy of the community has also increased since the presence of several Islamic boarding schools in that place.